A new music therapy engagement scale for persons with dementia. (25th May 2018) - Tan, Jane; Wee, Shiou-Liang; Yeo, Pei Shi; Choo, Juliet; Ritholz, Michele; Yap, Philip
ABSTRACT: Objectives: To develop and validate a new scale to assess music therapy engagement in persons with dementia (PWDs). Design: A draft scale was derived from literature review and >2 years of qualitative recording of PWDs during music therapy. Content validity was attained through iterative consultations, trial sessions, and revisions. The final five-item Music Therapy Engagement scale for Dementia (MTED) assessed music and non-music related elements. Internal consistency and inter-rater reliability were assessed over 120 music therapy sessions. MTED was validated with the Greater Cincinnati Chapter Well-being Observation Tool, Holden Communication Scale, and Participant Engagement Observation Checklist – Music Sessions. Setting and participants: A total of 62 PWDs (83.2 ± 7.7 years, modified version of the mini-mental state examination = 13.2/30± 4.1) in an acute hospital dementia unit were involved. Results: The mean MTED score was 13.02/30 ± 4.27; internal consistency (Cronbach's α = 0.87) and inter-rater reliability (intra-class correlation = 0.96) were good. Principal component analysis revealed a one-factor structure with Eigen value > 1 (3.27), which explained 65.4% of the variance. MTED demonstrated good construct validity. The MTED total score correlated strongly with the combined items comprising Pleasure, Interest, Sadness, and Sustained attention of the Greater Cincinnati Chapter Well-being Observation Tool ( rs = 0.88, p < 0.001). Conclusions: MTED is a clinically appropriate and psychometrically valid scale to evaluate music therapy engagement in PWDs.